DNA methylation QTL analysis identifies new regulators of human longevity. (11th March 2020) - Szymczak, Silke; Dose, Janina; Torres, Guillermo G; Heinsen, Femke-Anouska; Venkatesh, Geetha; Datlinger, Paul; Nygaard, Marianne; Mengel-From, Jonas; Flachsbart, Friederike; Klapper, Wolfram; Christensen, Kaare; Lieb, Wolfgang; et al.
Abstract: Human longevity is a complex trait influenced by both genetic and environmental factors, whose interaction is mediated by epigenetic mechanisms like DNA methylation. Here, we generated genome-wide whole-blood methylome data from 267 individuals, of which 71 were long-lived (90–104 years), by applying reduced representation bisulfite sequencing. We followed a stringent two-stage analysis procedure using discovery and replication samples to detect differentially methylated sites (DMSs) between young and long-lived study participants. Additionally, we performed a DNA methylation quantitative trait loci analysis to identify DMSs that underlie the longevity phenotype. We combined the DMSs results with gene expression data as an indicator of functional relevance. This approach yielded 21 new candidate genes, the majority of which are involved in neurophysiological processes or cancer. Notably, two candidates ( PVRL2, ERCC1 ) are located on chromosome 19q, in close proximity to the well-known longevity- and Alzheimer's disease-associated loci APOE and TOMM40 . We propose this region as a longevity hub, operating on both a genetic ( APOE, TOMM40 ) and an epigenetic ( PVRL2, ERCC1 ) level. We hypothesize that the heritable methylation and associated gene expression changes reported here are overall advantageous for the LLI and may prevent/postpone age-related diseases and facilitate survival into very old age.